Analisis Rasio Likuiditas Untuk Menilai Kinerja Keuangan Pada Koperasi Simpan Pinjam Tunggal Karya Desa Semamung Kecamatan Moyo Hulu Kabupaten Sumbawa - Putra, Yosrul Derita; Faturrahman, Fadli (CV. Kalimasada Group, 2024)
This study aims to find out how the Financial Performance of the Savings and Loans Cooperative in Semamung Village, Moyo Hulu District uses Liquidity Ratio Analysis. The method used in this study is a qualitative method with a descriptive approach. The data source for this study was primary data obtained from interviews, observation, and documentation techniques which were carried out directly with the Karya Savings and Loans Cooperative, Semamung Village, Moyo Hulu District, Sumbawa Regency. The results of this study are that the Financial Performance of the Karya Savings and Loan Cooperative, Semamung Village, Moyo Hulu District, Sumbawa Regency is said to be good when viewed from the Current Ratio and Quick Ratio, but the Cash Ratio is still said to be poor. In order to optimize research outcomes, previous research references are utilized to enhance understanding and ensure the smooth progression of the study in line with the intended objectives.